Synthesis, structure and physical properties of a low dimensional compound - Ramos Silva, Manuela; Coutinho, Joana T.; Pereira, Laura C.J.; Martín-Ramos, Pablo; Waerenborgh, João C. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2017)
The crystal structure of (μ3-oxo)hexakis(cyanoacetato-κO,O′)(cyanoacetato-κO)diaquatriiron(III) cyanoacetic acid shows the formation of trinuclear complexes in a hydrogen-bond network that bonds all the molecules in a 3D arrangement. For this complex, within whose clusters the whole magnetic interaction takes place, 57Fe Mössbauer spectroscopy shows that the Fe cations are in the S=5/2 state in the temperature range 2–295K. The asymmetric broadening of the absorption peaks below 80K is consistent with strong antiferromagnetic interactions between the metal spins. The magnetization measurements also show the antiferromagnetic character of the spin ensemble and an ST=1/2 magnetic ground state typical of triangular systems with similar J between Fe-Fe pairs. [Display omitted] •A novel cyanoacetato-based compound with Fe(III) has been synthesized.•Fe clusters are H-bonded in a 3D arrangement.•Mossbauer spectroscopy reveals that Fe cations are in the high spin, S=5/2, state.•Magnetic properties of trinuclear Fe complex are described by isosceles two-J model.•Fe(III) triangular system shows strong antiferromagnetic interactions with ST=1/2.